ANALISIS PERDEBATAN HADITS BEKAM SAAT BERPUASA DAN SIGNIFIKANSINYA TERHADAP STATUS HUKUM FIQH DALAM PERSPEKTIF IMAM MADZHAB - Qustulani, Muhammad (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This paper discusses the differences in the views of scholars about the status of invalid and whether or not people have cupping during the day of Ramadan. The first hadith that the Prophet once said “Afthara al-Hajim wa al Mahjum,” the fasting of people with cupping is invalidated when fasting, but in another hadith it is explained that the Prophet Muhammad used to cupping during the day when he was fasting in Ramadan, “ihtajam al-naby wa huwa sha’imun.” This study is a library of research that explains and compares the legal differences of juries from the existence of the two hadith. The conclusion of this study is (1) that both hadiths are included in the category of hadith shohih in the science of hadith, (2) differences in the use and perspective of fiqh scholars have an impact on differences in the legal status of fasting people who are in the daytime of Ramadan. The first group, such as the Hanbali school, Ishaq Ibn Rahawaih, Ibn Khuzaimah, Ibn al-Mundzir, and Ibn Taimiyah argued that the law of fasting was void, while other groups such as the Hanafiyah Madhab, Shafi’iyyah madhab, Malikiyah and al-Zhawahiriyah argued not to be void but makruh.